2022
DOI: 10.3389/fcvm.2022.949726
|View full text |Cite
|
Sign up to set email alerts
|

Non-vitamin K antagonist oral anticoagulants versus warfarin in atrial fibrillation patients with heart failure and preserved, mildly reduced, and reduced ejection fraction: A systemic review and meta-analysis

Abstract: BackgroundPatient prevalence of atrial fibrillation (AF) and heart failure (HF) is increasing, and anticoagulation for patients from heterogeneous backgrounds with both conditions remains controversial. In this meta-analysis, we are aiming to compare the effectiveness and safety of the non-vitamin K antagonist oral anticoagulants (NOACs) and warfarin in AF patients with HF and preserved (HFpEF), mildly reduced (HFmrEF), and reduced (HFrEF) ejection fraction.Methods and resultsWe systematically searched the Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(20 reference statements)
2
1
0
Order By: Relevance
“…Thus, although detailed echocardiographic data were not available in this subanalysis, most patients with HF in this study may have HFpEF or HF with mildly reduced ejection fraction (HFmrEF). A previous meta‐analysis including 10 studies showed that DOAC use was associated with lower risks for stroke or systemic embolism and major bleeding in patients with AF and HFpEF or HFmrEF 34 . Our subanalysis presents similar results to this meta‐analysis in elderly patients; however, further study may be required to elucidate the effectiveness of DOAC use in older patients with AF and HFrEF.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, although detailed echocardiographic data were not available in this subanalysis, most patients with HF in this study may have HFpEF or HF with mildly reduced ejection fraction (HFmrEF). A previous meta‐analysis including 10 studies showed that DOAC use was associated with lower risks for stroke or systemic embolism and major bleeding in patients with AF and HFpEF or HFmrEF 34 . Our subanalysis presents similar results to this meta‐analysis in elderly patients; however, further study may be required to elucidate the effectiveness of DOAC use in older patients with AF and HFrEF.…”
Section: Discussionsupporting
confidence: 77%
“…A previous meta-analysis including 10 studies showed that DOAC use was associated with lower risks for stroke or systemic embolism and major bleeding in patients with AF and HFpEF or HFmrEF. 34 Our subanalysis presents similar results to this meta-analysis in elderly patients; however, further study may be required to elucidate the effectiveness of DOAC use in older patients with AF and HFrEF. Third, recently emerging drugs such as angiotensin receptor-neprilysin inhibitor (ARNI) and sodiumglucose cotransporter-2 (SGLT-2) inhibitors were not used when the ANAFIE Registry was performed, 35,36 although apparent interaction has not been reported between SGLT-2 inhibitors or ARNI and OAC therapy.…”
Section: Discussionsupporting
confidence: 71%
“…In the review performed by Shantsila et al, OAC was a non-superior lowering-stroke option for HFpEF patients with sinus rhythm, with no information regarding the antithrombotic effects of OAC versus antiplatelets [ 10 ]. Non-vitamin K oral anticoagulant (NOAC) was a novel marketed anticoagulant for better safety outcomes but had no significant difference in systemic embolism risk among HFpEF patients with AF [ 26 ]. Due to the HFpEF heterogeneity and AF history, the efficacy of OAC for stroke reduction in HFpEF patients was still controversial, and hence more data regarding OAC therapy would be provided in future studies.…”
Section: Discussionmentioning
confidence: 99%